MEMAHAMI STUDI DOKUMEN DALAM PENELITIAN KUALITATIF - Nilamsari, Natalina (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2014)
Qualitative research is a method of research used to uncover the problems in working life government organizations,private sector, civil society, youth, women, sports, arts and culture, and others that can be used as a policyfor the sake of the common welfare. Calls "issues in qualitative research are temporary, tentative and will evolveor change after researchers were in the field".In a qualitative research methodology, there are a variety of datacollection methods / sources used. A Conceptual Introduction, mention at least four strategies with multi-datacollection in qualitative research methods: participant observation, in-depth interviews, the study documents andartifacts, as well as complementary techniques. In this article that will be discussed is the method of data collectionstrategy document. According, "the documentary is one method of data collection methods used in socialresearch methodology to explore historical data ".states that the document is a record of events that have alreadypassed in the form of text, images, or monumental works of a person. "